Teaching in preschool during the pandemic: interactions between teacher, students, families and screens - Blanca Araceli Rodríguez Hernández; Nadia Sarahí Ruiz Reyna (Universidad de Guadalajara, 2022)
The objective of this paper was to analyze the teaching practice of a preschool teacher in a private school in San Luis Potosi, Mexico, based on the dimensions of effective and represented work. From the analysis of the instructions and the simple self-confrontation, axes of analysis were identified that allowed an approach to the main challenges that the teacher faced with the online education developed during the pandemic by covid-19. The results of the work placed at the center of the discussion the teacher's challenges and concerns about the ways of teaching online literacy, the relationships with the students' families when working from home, and the interaction with technology in the virtual classroom. Taken together, the findings broaden the picture of teaching practices during social distancing and contribute to the empirical knowledge of this object of study as a result of the impact generated by the pandemic.